International Financial Reporting Standards Adoption and Earnings of Quoted Banks in Nigeria - Sanyaolu, O.A.; Iyoha, F. O.; Ojeka, Stephen A. (International Journal of Economics and Financial Issues, 2017)
The aim of this study is to examine the effect of adopted International Financial Reporting Standards (IFRS) adoption on the earning yield and earning per share of quoted banks in Nigeria. The study made use of cross sectional data obtained for a period of 6 years from 2009-2014, while the panel ordinary least method of analysis was used to examine the impact of IFRS adoption on the earnings of all 15 quoted banks in the Nigerian Stock Exchange. The study found a significant and positive relationship between IFRS adoption and the earning yield of quoted banks in Nigeria. The study also found a significant and positive relationship between IFRS adoption and earning per share of quoted banks in Nigeria. The study concludes that IFRS adoption has improved the decision making capability of the various stakeholders, thus, increasing investor confidence and the inflow of capital in the country through foreign direct investment. The study suggests that, in order to safeguard the suitable adoption of IFRS in Nigeria, competent Accountants and Auditors in IFRS are required in large number and that the Institute of Chartered Accountants of Nigeria (ICAN) must intensify it efforts in organising IFRS based training programmes for its members and other parties connected with corporate reporting. Keywords: Corporate Reporting, Adoption, Performance, Local GAAP, IFRS JEL Classifications: G23, M4